Redescription of the grassland leafhopper genus Doraturopsis Lindberg (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) with description of a new genus and species from China - Duan, Yani; Zhang, Yalin (Zootaxa, 2012)
The deltocephaline leafhopper genus Doraturopsis Lindberg (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) andspecies D. heros (Melichar) are redescribed, and a new genus and species Zahniserius cylindricus, gen. n., sp. n. fromChina, with an aedeagus similar to that of Doraturopsis, are described. Keys are provided to separate the genera of Chinese Chiasmini Distant and two species of Doraturopsis.